2019
DOI: 10.1177/2325967119873274
|View full text |Cite
|
Sign up to set email alerts
|

Different Suture Materials for Arthroscopic Transtibial Pull-out Repair of Medial Meniscal Posterior Root Tears: A Human Biomechanical Study

Abstract: Background: Transtibial pull-out repair of the medial meniscal posterior root (MMPR) has been largely assessed through biomechanical studies. Biomechanically comparing different suture types would further optimize MMPR fixation and affect clinical care. Purpose/Hypothesis: The purpose of this study was to determine the optimal suture material for MMPR fixation. It was hypothesized that ultra high–molecular weight polyethylene (UHMWPE) suture tape would be biomechanically superior to UHMWPE suture and standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…They were also in line with the efficacy of MMPRT repairs reported in past studies. 4,5 On the other hand, the results of the cyclic loading did not follow our hypothesis. Even though average displacement in the SUTURETAPE group was smaller than it was in the UltraBraid group, the use of UHMWPE suture tape did not contribute to a significant decrease in displacement during cyclic loading.…”
Section: Discussioncontrasting
confidence: 84%
“…They were also in line with the efficacy of MMPRT repairs reported in past studies. 4,5 On the other hand, the results of the cyclic loading did not follow our hypothesis. Even though average displacement in the SUTURETAPE group was smaller than it was in the UltraBraid group, the use of UHMWPE suture tape did not contribute to a significant decrease in displacement during cyclic loading.…”
Section: Discussioncontrasting
confidence: 84%
“…Partial meniscectomy has also been performed in patients with degenerative MMRTs and the symptom of a locking knee long before meniscal repair. Judging by the superiority of meniscal repair over partial meniscectomy as seen from the biomechanical data, 11 , 32 , 36 the clinical outcomes of meniscal repair are likely to be better than those of partial meniscectomy. Nevertheless, few studies have directly compared the results between meniscal repair and partial meniscectomy in patients with MMRTs.…”
mentioning
confidence: 99%
“…With the development of meniscal repair surgery, many suture devices and techniques have been used [17,18]. Several studies have been performed to investigate the clinical outcomes with different suture materials and repair techniques and have shown that the results are comparable with regard to the patient-reported outcomes and meniscal healing rate [19][20][21]. In our study, we used the FasT-Fix suture device for all patients with all-inside meniscal repair, which is the most widely used procedure.…”
Section: Discussionmentioning
confidence: 99%